Abstract 13114: Effectiveness of a Novel Decision Aid for Surrogate Decision Makers of Comatose Survivors of Cardiac Arrest: A Pilot Study of the “Tool to EMPOwer Surrogate Decision Makers” (TEMPO) - Perman, Sarah M; Shelton, Shelby; Siry-Bove, Bonnie; Mayer, Katherine; Matlock, Dan D; Haukoos, Jason S; Abella, Benjamin; Daugherty, Stacie; Havranek, Edward (Circulation (New York, N.Y.), 2021)
IntroductionSurrogate decision makers (SDMs) represent critical stakeholders in decision making for comatose survivors of cardiac arrest, yet these individuals are often unprepared for decision making and unfamiliar with the complexity of post-cardiac arrest care. To that end, we created a decision aid for SDMs intended to inform and support evidence-based decision making for comatose survivors of cardiac arrest. MethodsWe conducted a pilot trial to measure real world effectiveness of the Tool to EMPOwer (TEMPO) Surrogate Decision Makers, by measuring knowledge and acceptability. Individuals were enrolled who self-identified as the SDM for a comatose survivor of OHCA admitted to an academic tertiary care hospital. Participants completed a pre-intervention survey prior to the provision of TEMPO, and a post-intervention survey approximately 24 hours after exposure to the intervention. Pre-survey questions included SDM demographics and an 8-question knowledge survey. Post-intervention surveys included the same knowledge questions, the Ottawa Acceptability of Decision Aid tool, and questions to measure if SDMs shared TEMPO with others. This study was approved by the Colorado Multiple Institutional Review Board and registered at Clinicaltrials.gov (NCT03908346). ResultsTwenty SDMs were enrolled between 9/1/2020 and 6/7/2021. One subject did not complete the post-intervention survey therefore 19 subject responses were analyzed for the purpose of this report. Participants were 85.0% Female, 47.4 +/- 14.8 years, and 45.0% were the spouse of the patient. In the 8-question knowledge survey, results improved from 57.2% correct to 90.8% correct after exposure to TEMPO (p<0.001). Using the Ottawa Acceptability Tool, 89.5% of participants stated TEMPO was useful in decision-making and 94.7% reported that TEMPO made their decision “easier”. Most (79.0%) participants reported they shared the DA with another family/friend in-person, while some (52.6%) reported they shared content with another person by telephone. ConclusionInitial pilot data on the efficacy of the Tool to EMPOwer Surrogate Decision Makers of comatose survivors of cardiac arrest shows significant promise in improving knowledge and supporting decision-making.